Chinese herbal medicine (Guben Qushi Huayu formula) combined with Ixekizumab in reducing psoriasis vulgaris relapse: Protocol for a mixed-methods research study - Li, Ziqing; Guan, Kewen; Deng, Hao; Ye, Shuyan; Deng, Jingwen; Yao, Danni; Yan, Yuhong; Chen, Haiming; Lu, Chuanjian; Yu, Jingjie (Frontiers in Pharmacology, 2025)
IntroductionPsoriasis vulgaris (PV) is an inflammatory, chronically relapsing dermatological disease associated with significant comorbidities. Ixekizumab is recommended as the first-line therapy for severe PV, but encounters persistent challenges with relapse after treatment discontinuation. In clinical practice, Chinese herbal medicine (CHM) including Guben Qushi Huayu formula (GQHF) has been demonstrated effective in reducing PV relapse. However, there remains a scarcity of high-level evidence-based study in this respect. Therefore, this study aims to preliminarily evaluate the feasibility and acceptability of Ixekizumab combined with GQHF in reducing PV relapse.Methods and analysisThis study employs a mixed-method research (MMR) design, encompassing both quantitative and qualitative studies. The quantitative study consists of a randomized controlled trial involving 50 participants with severe PV, who will be randomly allocated to the intervention group (Ixekizumab plus GQHF) and the control group (Ixekizumab plus GQHF placebo) in a 1:1 ratio. Relapse rate is the primary endpoint. The qualitative study involves semi-structured interviews to concurrently explore the acceptability of the application of Ixekizumab combined with GQHF among the enrolled participants.DiscussionThis pilot study utilizes MMR to investigate the effect of Ixekizumab combined with GQHF in reducing PV relapse. The findings are expected to provide valuable clinical evidence and a novel therapeutic option for PV. Moreover, it is our intention to conduct a larger MMR trial to further strengthen the clinical evidence and broaden the application of Ixekizumab in combination with GQHF.Clinical Trial Registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2100054950.